Resposta :
Explicação passo-a-passo:
4) 4.(x + 2) = 4x + 8
5) 2 . (2x + 1) + 2 . (x + 1) =
4x + 2 + 2x + 2 =
6x + 4
6) V = (2x + 1) . 3x . (x + 2) =
V = (6x² + 3x).(x + 2)
V = 6x³ + 12x² + 3x² + 6x
V = 6x² + 15x² + 6x
Resposta:
Explicação passo a passo:
[tex]4)[/tex]
[tex]P=4.(x+2)[/tex]
[tex]P=4x+8[/tex]
[tex]5)[/tex]
[tex]P=(2x+1)+(2x+1)+(x+1)+(x+1)=[/tex]
[tex]P=6x+4[/tex]
[tex]6)[/tex]
[tex]V = (2x+1).(3x).(x+2)[/tex]
[tex]V =(6x^{2} +3x).(x+2)[/tex]
[tex]V=6x^{3} +12x^{2} +3x^{2} +6x[/tex]
[tex]V=6x^{3} +15x^{2} +6x[/tex]